A method to eliminate unsprung adverse effect of in-wheel motor-driven vehicles. Issue 4 (December 2018) - Nie, Shida; Zhuang, Ye; Chen, Fan; Wang, Yong; Liu, Shu
In-wheel motor-driven vehicles are the development trend for future vehicles due to its high energy efficiency and low emission as well as its flexibility to achieve independent steering, driving, etc. However, the weighted wheel of in-wheel electric vehicles involves more unexpected unsprung vibrations, which imposes adverse effect on vehicle ride comfort. In addition, there exists an invariant point around the unsprung resonance frequency in both controlled and uncontrolled suspensions, which greatly limits the elimination of unsprung adverse effect of in-wheel electric vehicles. In this paper, a combined structure is proposed to eliminate the unsprung adverse effect. The structure is composed of the vehicle suspension and a tuned mass damper, which are both controlled by a sliding mode controller, aiming at eliminating the unsprung adverse effect as well as improving ride comfort across the whole frequency spectrum. The tunes mass damper is used to get rid of the constraint of the invariant point. The simulation and hardware-in-the-loop results show that the root mean square of the sprung mass acceleration and tire deflection is reduced by 31.2% and 2.2% respectively, which indicates that the proposed method is effective and ride comfort is greatly improved.